2004
DOI: 10.1007/s00259-004-1577-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-FDG PET in the detection of peritoneal carcinomatosis

Abstract: We found that use of an intra-abdominal FDG uptake cut-off value for SUVmax of >5.1 assists in the diagnosis of peritoneal carcinomatosis. FDG PET may play an important role in the clinical management of patients with suspected peritoneal carcinomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 22 publications
1
37
0
7
Order By: Relevance
“…FDG PET and CT had a sensitivity of 66.7%, specificity of 94.1%, and PPV of 92.3%. These results provide important information to the management of patients with peritoneal carcinomatosis [19] .…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET and CT had a sensitivity of 66.7%, specificity of 94.1%, and PPV of 92.3%. These results provide important information to the management of patients with peritoneal carcinomatosis [19] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that the routine use of FDG PET is unsuitable as a diagnostic imaging procedure for lesion characterization, evaluation of the extent of the disease and the relationship with the adjacent organs (34). More recently, several studies examining the detection of peritoneal carcinomatosis by PET have demonstrated that the use of combined PET and CT showed a sensitivity of 67-78% and a PPV of 92-95% (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have shown that the use of PET does not improve the diagnostic accuracy, while others have shown that PET can supplement the information obtained by CT and MRI (19)(20)(21)(22)(23). Some recent studies have demonstrated that for peritoneal carcinomatosis, the use of combined PET and CT may play an important role in the clinical management of patients (24,25). However, to the best of our knowledge, there are few reports that have examined a comparison of the use of MRI and integrated PET/CT to predict the presence of peritoneal carcinomatosis resulting from primary ovarian cancer (26).…”
mentioning
confidence: 99%
“…Scintigraphic signs: focal uptake [13], diffuse peri-hepatic curvilinear uptake [11], sub parietal (epiploic) uptake or the presence of a straight line sign [15,16]; and morphologic signs: peritoneal nodal tissue, fat infiltration, epiploic thickening, ascite [17]. The two reviewers looked for lesions across the whole of the peritoneal cavity with particular attention to the level of the left and right paracolic gutter, the peri-hepatic area, the pelvis and the omentum.…”
Section: Signs Indicating Pc Werementioning
confidence: 99%
“…Promising results highlight the use of 18F-FDG PET to evaluate PC extension pre-operatively [7,8] although only a few reports have been published on the diagnostic performance of 18F-FDG PET/CT. Sensitivities reported have varied from unacceptably low (35%) to 100% [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%